Bolivia Poverty Assessment : Establishing the Basis for Pro-Poor Growth - Arias, Omar S.; Bendini, Magdalena (World Bank, Washington, DC, 2012)
This brief discussion of Bolivia's poverty assessment notes that Bolivia's growth prospects remain vulnerable to domestic instability and external circumstances. Because of the depth and breadth of poverty in Bolivia, and the skewed income distribution, high GDP per capita growth rates about 4 to 5 percent per year are necessary in the medium and longer term, if the country's poverty level is to be significantly reduced. The national MDG target of reducing the incidence of extreme poverty in half by 2015 could be achieved with growth rates in this range, along with other pro-poor policy interventions. Even higher per capita growth is needed to meet the MDG of reducing poverty in half. Economic simulations indicate that the country can improve its future growth potential through a comprehensive strategy of mutually-reinforcing reforms that includes macroeconomic stability.